2021
DOI: 10.1093/jac/dkab089
|View full text |Cite
|
Sign up to set email alerts
|

Probability of pharmacological target attainment with flucloxacillin in Staphylococcus aureus bloodstream infection: a prospective cohort study of unbound plasma and individual MICs

Abstract: Objectives MSSA bloodstream infections (BSIs) are associated with considerable mortality. Data regarding therapeutic drug monitoring (TDM) and pharmacological target attainment of the β-lactam flucloxacillin are scarce. Patients and methods We determined the achievement of pharmacokinetic/pharmacodynamic targets and its association with clinical outcome and potential toxicity in a prospective cohort of 50 patients with MSSA-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…25 Recent pharmacologic studies showed that in a majority of patients, a reduction of the flucloxacillin dose would still lead to attainment of the optimal pharmacodynamic endpoint. 26,27 Also, our study and other reports suggest an increased risk of adverse events with a higher flucloxacillin dose and flucloxacillin concentration. 27,28 Although the flucloxacillin concentration measurements in our study were limited, Figure 1A…”
Section: Discussionsupporting
confidence: 73%
“…25 Recent pharmacologic studies showed that in a majority of patients, a reduction of the flucloxacillin dose would still lead to attainment of the optimal pharmacodynamic endpoint. 26,27 Also, our study and other reports suggest an increased risk of adverse events with a higher flucloxacillin dose and flucloxacillin concentration. 27,28 Although the flucloxacillin concentration measurements in our study were limited, Figure 1A…”
Section: Discussionsupporting
confidence: 73%
“…This problem is minimized in animal infection model or dynamic in vitro infection model studies aimed at elucidating the predictive PK-PD index and target values for various magnitudes of bacterial kill by ensuring that several bacterial strains are included in the study to inform setting of PK-PD targets and breakpoints (Zhao et al, 2016;Mouton et al, 2018b;Jorda and Zeitlinger, 2020). However, an inaccurate estimate from a single determination of MIC for an isolate from a particular patient is problematic in the clinical application of MIC-based PK-PD targets within the framework of what has been described as therapeutic drug monitoring (TDM) (Mouton et al, 2018b;Roberts et al, 2019;Märtson et al, 2020;Seeger et al, 2021a;Goutelle et al, 2021;Jorgensen et al, 2021;Moser et al, 2021). Thus, if an isolate from an infected patient returns an MIC estimate from an assay which has a typical error range of two dilutions (i.e., potentially a 4-fold range of reported MIC values), it follows that the PK-PD driven target plasma concentration for that patient would vary 4-fold if the PK-PD index for the antibiotic is fAUC/MIC or fC max /MIC.…”
Section: Mic: a Highly Problematic Measure Of Antibacterial Pd Activitymentioning
confidence: 99%
“…The values found for the MICs are in line with the values reported previously in literature, however large distributions are lacking. A study in 37 MSSA isolates reported values between 0.06 and 0.25 mg/L [ 9 ], while in case reports, higher values for the flucloxacillin MIC were reported of up to 1 mg/L [ 10 , 11 ]. Because of the lack of data on MIC distribution for flucloxacillin, several studies use MIC values for oxacillin instead with an ECOFF of 2 mg/L [ 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%